The Growth Rate Of Branchionus Plicatilis O.F. Muller Population With The Addition Of A Mixture Of Yeast, Chicken Manure Fertilizer, Urea, And Triple Super Phosphate (CAKAP) (Talenta Publisher, 2020)
The study of the growth rate of Branchionus plicatilis O.F. Muller population with the addition of a mixture of yeast, chicken manure fertilizer, urea, and triple super phosphate (CAKAP) was conducted in June 2012. Four treatments namely MK, MP1, Mp2, and MP3 were used in this experiment. MP1 consisted of CAKAP medium, 0.3 g/2L of yeast; MP1 consisted of CAKAP medium, 0.3 g/2L of yeast, and 0.1 ml/2L of fish oil. MP2 and MP3 have the composition as MP1 but show different concentrations of fish oil which were 0.2 and 0.3 ml/2L each. Every treatment had six replicates. The result showed that the highest growth rate of Branchionusplicatilis O F Muller was obtained from the first observation (day 2) of MP2 medium with the rate 2.605 individual x 2 x 10-3 per day while the lowest one was shown by MP3 medium which was 2.282 individual x 2 x 10-3 per day.